Pompe Disease Could Mimic Exam Findings of Amyloidosis: Two Rare Diagnoses Bona Fide - Jithma P. Abeykoon; Narjust Duma; Jennifer A. Tracy; Margherita Milone; Ronald Go (Case Reports in Hematology)
A 70-year-old female presented with a three-year history of evolving macroglossia causing dysphagia and dysarthria, with proximal muscle weakness. Given the classic physical finding of macroglossia, the patient underwent extensive evaluation for amyloidosis which proved to be negative apart from a bone marrow biopsy which stained positive for transthyretin without amino acid sequence abnormality, thus giving wild-type transthyretin amyloidosis. Since the wild-type transthyretin amyloidosis could not entirely explain her clinical presentation and evaluation, further studies were conducted in a sequential manner, thus leading to a diagnosis of Pompe disease explaining her presenting signs and symptoms including her macroglossia. Through this fascinating case, we attempt to highlight the approach for the diagnoses of two rare diseases in a patient by emphasizing the importance of having a broad differential diagnosis when presented with findings which may have been thought as pathognomonic for certain diseases.